A LIQUID-CRYSTALLINE FERROCENE DERIVATIVE WITH A CHIRAL SMECTIC C-PHASE - IMRIE, C; LOUBSER, C (Journal of the Chemical Society. Chemical communications, 1994)
The synthesis of the first liquid crystalline derivative of ferrocene with a chiral smectic C phase is reported.